(untitled) (Research, Society and Development, 2020)
Objective: To analyze Covid-19 incidence and mortality and its relationship with social indicators of the municipalities of Santa Catarina. Methods: An ecological study with data from the 1st to 14th epidemiological weeks in the year 2020. The independent variables were sociodemographic indicators. The outcomes were the incidence and mortality rates for Covid-19 for each municipality. Negative inflated zero binomial regression was used, considering 95% confidence intervals and thematic maps were created. Results: In the period, 17,368 cases and 253 deaths were recorded. The incidence of Covid-19 was associated with greater population size, demographic density, and Gini index, and decreased with increasing aging rates. Mortality, on the other hand, was associated with an increase in population size and demographic density. Conclusion: Although Covid-19 has potential for dissemination to all municipalities in Santa Catarina, social and demographic characteristics are related to pandemic behavior.